2015
DOI: 10.1186/s12906-015-0528-4
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of in-vitro anti-inflammatory bioactive compounds isolated from Jatropha curcas L. plant root

Abstract: BackgroundThe Jatropha curcas plant or locally known as “Pokok Jarak” has been widely used in traditional medical applications. This plant is used to treat various conditions such as arthritis, gout, jaundice, wound and inflammation. However, the nature of compounds involved has not been well documented. Hence, this study was conducted to investigate the anti-inflammatory activity of different parts of J. curcas plant and to identify the active compounds involved.MethodsIn this study, methanol (80%) extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 20 publications
2
39
0
1
Order By: Relevance
“…Neuroprotector [90], anti-inflammatory [95] Plasticizer for vinyl, cellulosic, and acrylate resins and synthetic rubber [97] obtained in the hydroethanolic ultrasound extracts, and the highest TAC was obtained in the acid extract. e extracts evaluated exhibited good antioxidant capacity with both high inhibitory activity against ABTS•+ radical cations and strong scavenging activity against DPPH radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotector [90], anti-inflammatory [95] Plasticizer for vinyl, cellulosic, and acrylate resins and synthetic rubber [97] obtained in the hydroethanolic ultrasound extracts, and the highest TAC was obtained in the acid extract. e extracts evaluated exhibited good antioxidant capacity with both high inhibitory activity against ABTS•+ radical cations and strong scavenging activity against DPPH radicals.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the comparison of differences in acute toxicity [6,7], anti-inflammatory and analgesic effects between RAR and vinegar-processed RAR was conducted systematically. The changes in the chemical composition of RAR and vinegarprocessed RAR were investigated, and the mechanism of vinegar processing was explored preliminarily to provide available scientific support for the mechanism study and clinical application of vinegar-processed RAR [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…From Table 3, it is found that the concentrations of the compounds extracted from prickly pear peels with UASE ( Figure 7) are not similar to that of the soxhlet extraction technique ( Figure 8). Compounds such as phytol, azulene, 9-eicosyne, (Sivakumar, Jebanesan, Govindarajan, & Rajasekar, 2011)Anti-inflammatory and cytotoxicity activities (Othman, Abdullah, Ahmad, Ismail, & Zakaria, 2015). as palmitic acid, which is widely used as a flavoring and an antiinflammatory agent.…”
Section: Identification Of Phytochemical Compoundsmentioning
confidence: 99%
“…as palmitic acid, which is widely used as a flavoring and an antiinflammatory agent. It also possesses antibacterial and antifungal (Sivakumar et al, 2011) and cytotoxicity properties (Othman et al, 2015). (Parthipan & Suky, 2015;Wei et al, 2011).…”
Section: Identification Of Phytochemical Compoundsmentioning
confidence: 99%